Proposed Methodology to Quantify the Amount of Methane Seepage by Understanding the Correlation Between Methane Plumes and Originating Seeps - Aoyama, Chiharu; Maeda, Nidomu (Frontiers in Earth Science, 2021)
The authors propose the following steps to quantify the amount of methane seepage accurately. First of all, methane plumes in the Exclusive Economic Zone (EEZ) of Japan are mapped out using acoustic devices such as quantitative echo sounders and multibeam sonars. Secondly, methane bubbles of a few millimeters in diameter from methane seeps at seafloor are collected and sampled using a cone-shaped collector with 20 cm in diameter, operated by Remotely Operated Vehicle (ROV). If we can identify the number of seep mouths that form into one single plume, we will be able to quantify the methane seepage from one plume. Based on this result, calibration of the mean backscattering strength and the amount of seeping methane from methane plumes becomes possible and will be applied to the mapped plumes in order to estimate the methane seepage in the EEZ of Japan. Once this calibration is established, it can be applied to the methane plumes observed worldwide, and methane seepage can be quantified simply by acoustic observations of methane plumes. In this study, a method to verify the correlation between methane plumes and methane seeps is introduced, as well as a method to locate methane seeps effectively using the Target Position function of a quantitative echo sounder. The authors intend to use this as the basic data for establishing a method to estimate the amount of methane released from a methane plume by observing the methane plume acoustically.